Solid oxide cell fuel electrode, half cell and cell preparation method
By preparing Ni-Fe or Ni-Cu alloy layer in the fuel electrode of solid oxide battery, the problem of interface cracks between Ni particles and oxygen ion conductor oxides is solved, the stability and electrochemical performance of the battery are improved, and high efficiency is achieved electrochemical reaction.
Patent Information
- Application Number
- CN202411578850.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In the reducing atmosphere of solid oxide batteries, cracks occur between Ni particles and oxygen ion conductor oxides, resulting in separation of the electrochemical reaction interface and reducing battery performance.
Ni-Fe or Ni-Cu alloy layer is prepared on the surface of Ni particles, and Ni-Fe and Ni-Cu are coated with Ni particles, thereby improving the bonding ability of metals and ceramics and reducing cracks.
The wettability of Ni particles and oxygen ion conductor oxide ceramic matrix is improved, the crack rate during the redox cycle is reduced, the electrochemical activity of the battery is maintained, and the voltage degradation rate within 1,000 hours is not greater than 0.025V/kh. The voltage for 1000 hours is not greater than 1.3V.
Smart Images

Figure CN119252939A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a solid oxide fuel cell fuel electrode, a half cell and a cell preparation method. Background Art
[0002] Solid oxide cell (SOC) is a fully solid-state ceramic device that has the dual functions of solid oxide fuel cell (SOFC) and solid oxide electrolyzer (SOEC). It has broad application prospects and is one of the core technologies for the future hydrogen energy industry and power industry. SOFC can directly convert the chemical energy in the fuel into electrical energy without being restricted by the Carnot cycle, so the energy conversion efficiency is very high, and it can achieve efficient and rapid conversion between fuel and electricity. It is an important low-carbon energy technology. It can significantly alleviate the problems of large energy loss and ecological damage when traditional fuels such as coal and oil are burned.
[0003] In the electrolytic cell mode, SOEC is a reversible process of SOFC, which can effectively convert electrical energy (especially electrical energy obtained from intermittent renewable energy sources such as solar and wind power) into chemical energy (such as H2, CO, etc.). Under external electrical load, SOEC can electrolyze H2O or CO2 to generate H2 or CO and O2. At the same time, the all-solid-state characteristics of SOC have the advantages of simple preparation method, convenient operation, high reliability and easy maintenance, and have received widespread attention and research. However, in a reducing atmosphere, NiO is reduced to Ni. When the SOC operates in an electrolysis condition, obvious gaps or peeling will occur between the Ni particles in its fuel electrode and the oxygen ion conductor oxide, such as Figure 1 As shown in the figure, the electrochemical reaction interface is reduced after separation, resulting in performance degradation. Therefore, the structure of the solid oxide battery should be improved so that the metal and ceramic can be better combined, the problem of metal-ceramic interface separation can be reduced, and the battery stability can be improved. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a solid oxide battery fuel electrode, a half-cell and a battery preparation method, by preparing a Ni-Fe or Ni-Cu alloy layer on the surface of the Ni particles of the fuel electrode to solve the problem of cracks generated at the interface between the Ni particles and the oxygen ion conductor oxide during electrolysis in a reducing atmosphere.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] In one aspect, the present invention provides a solid oxide fuel cell electrode,
[0007] Under a reducing atmosphere, the fuel electrode of the solid oxide battery comprises Ni particles and oxygen ion conductor oxide, the surface of the Ni particles has a Ni-Fe or Ni-Cu alloy layer; the thickness of the Ni-Fe or Ni-Cu alloy layer is 10-200nm.
[0008] Furthermore, the oxygen ion conductor oxide is YSZ or GDC.
[0009] On the other hand, the present invention discloses a method for preparing the above-mentioned solid oxide cell fuel electrode, comprising: preparing alloy powder; mixing the alloy powder with oxygen ion conductor oxide powder to prepare a fuel electrode membrane; sintering the fuel electrode membrane; the above-mentioned fuel electrode can be obtained under a reducing atmosphere.
[0010] Furthermore, the preparation method of the alloy powder comprises: mixing NiO powder with a nitrate solution of Fe or Cu, separating the solid, drying and calcining to obtain alloy powder; or mixing NiO powder with a nitrate solution of Fe or Cu, separating the solid, drying, and calcining to obtain an alloy powder intermediate; repeating the following process no more than three times: mixing the alloy powder intermediate with a nitrate solution of Fe or Cu, separating the solid, drying and calcining; and finally obtaining alloy powder.
[0011] Furthermore, the NiO powder is immersed in a 0.5-2.0 mol / L Fe or Cu nitrate solution, stirred at 70-120° C. and 300-500 r / min for at least 3 hours; and then dried and calcined at 700-900° C. for 5-6 hours.
[0012] Furthermore, the preparation of a fuel electrode membrane by mixing the alloy powder with the oxygen ion conductor oxide powder includes: adding the alloy powder and the oxygen ion conductor oxide powder at a mass ratio of 66:(30-40), adding a binder, a plasticizer and a dispersant to obtain a fuel electrode slurry and make a fuel electrode membrane.
[0013] Furthermore, the fuel electrode membrane sintering process is: heating to 1200-1500° C. at a rate not greater than 20° C. / min and maintaining for 5-20 hours.
[0014] On the other hand, the present invention discloses a method for preparing a solid oxide half-cell, including: preparing a fuel electrode support layer; preparing a fuel electrode, wherein the fuel electrode is the fuel electrode or the fuel electrode prepared by the preparation method; preparing an electrolyte layer; and performing a multi-step hot isostatic pressing treatment and sintering on the support layer, the fuel electrode and the electrolyte layer.
[0015] Furthermore, the hot isostatic pressing process is: maintaining at 50-85°C and a pressure of 10-60MPa for at least 30 minutes.
[0016] Finally, the present invention discloses a method for preparing a solid oxide battery, comprising: preparing a solid oxide half-cell by any of the above-mentioned preparation methods; preparing an oxygen electrode functional layer on the surface of the electrolyte layer of the solid oxide half-cell by screen printing, and then sintering at a temperature of 1000-1150°C for 1.5-3.0h.
[0017] Compared with the prior art, the technical solution provided by the present invention brings the following beneficial effects: the present invention solves the problem of cracks generated at the interface between Ni particles and oxygen ion conductor oxides in the prior art by preparing Ni-Fe and Ni-Cu alloys on the surface of Ni particles in the fuel electrode. Specifically, in a reducing atmosphere, NiO coated with Fe2O3 or CuO is reduced to generate Ni particles coated with Ni-Fe and Ni-Cu. Electrochemical driving in an electrolysis mode causes separation of Ni from the oxide interface. The Ni-Fe and Ni-Cu alloy layers can improve the interface between Ni particles and oxygen ion conductor oxide ceramics. The wettability of the porcelain matrix is improved, the bonding ability between the two is improved, and the probability of cracks in the subsequent redox cycle is reduced; secondly, the Ni-Fe and Ni-Cu layers have a certain coordination ability to coordinate the deformation between the two phases. In order to achieve the above-mentioned technical effect, the present application limits the thickness of the Ni-Fe and Ni-Cu alloy layers. If the thickness is too thin, the coordination effect is limited. If the thickness is too thick, the electrochemical activity of the solid oxide battery is affected. When the solid oxide battery provided by the present invention is used for electrolysis of water, the degradation rate is not more than 0.025V / kh, and the voltage value at 1000h is not more than 1.3V. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a SEM image of a fuel electrode in the prior art, where the ellipse marks the location where the crack occurs;
[0020] Figure 2 A schematic diagram of the structure of a solid oxide half-cell provided in Example 1 of the present invention;
[0021] Figure 3 This is a SEM image of the solid oxide half-cell provided in Example 1 of the present invention;
[0022] Figure 4 This is a SEM image of the fuel electrode of the solid oxide cell provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific implementation of the present invention is not limited to the specific embodiments given here, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the disclosed specific embodiments.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and do not limit the present invention.
[0025] like Figure 2 The present invention provides a solid oxide cell fuel electrode. Under a reducing atmosphere, the fuel electrode of the solid oxide cell comprises Ni particles and oxygen ion conductor oxides, and the surface of the Ni particles has a Ni-Fe or Ni-Cu alloy layer; the thickness of the Ni-Fe or Ni-Cu alloy layer is 10-200nm.
[0026] The present invention prepares Ni-Fe and Ni-Cu alloys on the surface of Ni particles in the fuel electrode to solve the problem of cracks generated at the interface between Ni particles and oxygen ion conductor oxide phases in the prior art. Specifically, in a reducing atmosphere, NiO coated with Fe2O3 or CuO is reduced to generate Ni particles coated with Ni-Fe and Ni-Cu. Electrochemical drive in the electrolysis mode causes separation of Ni and the oxide interface. The Ni-Fe and Ni-Cu alloy layers can improve the wettability of the Ni particles and the oxygen ion conductor oxide ceramic matrix, enhance the bonding ability between the two, and reduce the probability of cracks generated in the subsequent redox cycle process. Secondly, the Ni-Fe and Ni-Cu layers have a certain coordination ability to coordinate the deformation between the two phases. In order to achieve the above technical effects, the present application limits the thickness of the Ni-Fe and Ni-Cu alloy layers. If the thickness is too thin, the coordination effect is limited. If the thickness is too thick, the electrochemical activity of the solid oxide battery is affected. When the solid oxide battery provided by the present invention is used to electrolyze water, the degradation rate is not more than 0.025V / kh, and the voltage at 1000h is not more than 1.3V.
[0027] Specifically, the oxygen ion conductor oxide is YSZ or GDC, and preferably, YSZ is 8YSZ.
[0028] The present invention also provides a method for preparing the solid oxide fuel cell fuel electrode, comprising:
[0029] S10 prepares alloy powder.
[0030] The preparation methods of the alloy powder include two methods:
[0031] The first method is to mix NiO powder with Fe or Cu nitrate solution, separate the solid, dry and calcine it to obtain alloy powder;
[0032] The second method is: mixing NiO powder with a nitrate solution of Fe or Cu, separating the solid and drying it, and then calcining it after drying to obtain an alloy powder intermediate; repeating the following process no more than three times: mixing the alloy powder intermediate with a nitrate solution of Fe or Cu, separating the solid and drying and calcining it; finally obtaining an alloy powder.
[0033] Specifically, the NiO powder is immersed in a 0.5-2.0 mol / L Fe or Cu nitrate solution, stirred at 70-120° C. and 300-500 r / min for at least 3 hours; and then dried and calcined at 700-900° C. for 5-6 hours.
[0034] The nitrate solution of Fe or Cu generates NiO coated with Fe2O3 or CuO during the subsequent calcination process. It should be pointed out that the calcination in the present application can be carried out in an air atmosphere or an oxygen atmosphere. The present application limits the calcination temperature and calcination time. Fe2O3 or CuO is deposited on the NiO surface through calcination. However, it should be noted that at this time, Fe2O3 or CuO and NiO do not form a diffusion layer. The main consideration is that the heating in the subsequent preparation process of the solid oxide battery causes atomic diffusion. If the alloy component close to the ceramic phase does not meet the design requirements, the wettability is still poor, so it is difficult to control.
[0035] S11: mixing the alloy powder with oxygen ion conductor oxide powder to prepare a fuel electrode membrane.
[0036] The alloy powder and the oxygen ion conductor oxide powder are added in a mass ratio of 66:(30-40), and a binder, a plasticizer and a dispersant are added to obtain a fuel electrode slurry and a fuel electrode membrane. Specifically, the binder is polyethylene glycol, the addition amount is 10-15wt%, the plasticizer is dimethyl phthalate, the addition amount is 12-15wt%, and the dispersant is triethanolamine, the addition amount is 8-12wt%, and then the zirconium oxide ball milling beads are used for ball milling for at least 36 hours, wherein the material-ball ratio is 1:(0.9-1.1) to ensure the uniformity of mixing, and the edges and corners of the powder can be polished to improve the uniformity of the thickness of the Ni-Fe or Ni-Cu alloy layer. Preferably, when using a nitrate solution of Fe, Fe2O3 is added, and when using a nitrate solution of Cu, CuO is added. On the one hand, this has the effect of aiding firing, and on the other hand, Ni-Fe or Ni-Cu phases are generated in a post-reducing atmosphere to facilitate the electrolysis process. In particular, the composition of one side of the Ni-Fe alloy layer combined with the ceramic must have good wettability with the ceramic phase. Using the same source of oxides for aiding firing can reduce the difficulty of preparing an alloy layer that meets the requirements.
[0037] Preferably, the particle size range of the alloy powder in the present invention is 5-20 μm, and the particle size range of the cationic conductor oxide powder is 10-30 μm, and the above particle size ranges are achieved by sieving through a sieve.
[0038] S12: sintering the fuel electrode membrane to obtain the fuel electrode membrane.
[0039] The sintering process of the fuel electrode membrane is: heating to 1200-1500°C at a rate of no more than 20°C / min and maintaining for 5-20 hours. The above process satisfies that the Ni content of the Ni-Fe or Ni-Cu alloy layer of the reduced Ni particles close to the ceramic matrix is about 30-70% to improve the wettability of the Ni particles and the ceramic matrix, while the Ni-Fe or Ni-Cu alloy layer coordinates the Ni particles and the ceramic phase matrix to avoid cracks under electrolysis conditions.
[0040] It should be pointed out that in the embodiment of the present invention, Fe2O3 or CuO is used to form a diffusion layer with NiO. Since it is difficult to control the direct use of Fe or Cu particles to form a diffusion layer with Ni, that is, the Fe or Cu particles are too small compared to Fe2O3 or CuO, and the diffusion coefficient is large, it is difficult to control. However, the use of oxides can effectively control the thickness of the diffusion layer formed by Fe2O3 or CuO and NiO, thereby controlling the thickness of the Ni-Fe or Ni-Cu alloy layer prepared in a reducing atmosphere to 10-200nm.
[0041] The present invention also provides a method for preparing a half-cell, comprising:
[0042] S20 prepares a fuel electrode support layer.
[0043] S21: preparing a fuel electrode, using the above fuel electrode or the fuel electrode prepared by the above preparation method. It should be noted that the above fuel electrode does not need to be reduced in a reducing atmosphere, and can be directly reduced after the solid oxide battery is prepared.
[0044] S22 prepares an electrolyte layer.
[0045] S23: performing a multi-step hot isostatic pressing treatment and sintering on the support layer, the fuel electrode and the electrolyte layer.
[0046] The hot isostatic pressing process is: maintaining at 50-85°C and 10-60MPa pressure for at least 30 minutes. The sintering process is: maintaining at 1200-1500°C for 5-20 hours.
[0047] The multi-step hot isostatic pressing is to stack the support layer and the fuel electrode for hot isostatic pressing. After the treatment is completed, the electrolyte layer is placed on one side of the fuel electrode, and then hot isostatic pressing is performed.
[0048] It is understandable that the preparation methods of the support layer, fuel electrode, and electrolyte layer involved in the embodiments of the present invention include but are not limited to: one or more of: tape casting, dry pressing, screen printing, spin coating, spraying, and vapor deposition.
[0049] For illustration, in the embodiment of the present invention, the fuel electrode support layer uses NiO-3YSZ, wherein the mass ratio of NiO powder to 3YSZ powder is 56: (40-50) and weighed and mixed, and then a dispersant, a plasticizer and a binder are added to make a fuel electrode support layer casting slurry, and zirconium oxide ball milling beads are added for ball milling for at least 36 hours. The dispersant is preferably triethanolamine, and the addition amount is 8-12wt%, the plasticizer is dimethyl phthalate, and the addition amount is 13-17wt%, and the binder is polyethylene glycol, and the addition amount is 10-15wt%.
[0050] The electrolyte layer is made of 8YSZ, and a dispersant, a plasticizer and a binder are added to make an electrolyte layer casting slurry, and then zirconium oxide ball milling beads are added for at least 36 hours. The dispersant is preferably triethanolamine, and the addition amount is 8-10wt%, the plasticizer is dimethyl phthalate, and the addition amount is 10-15wt%, and the binder is polyethylene glycol, and the addition amount is 8-10wt%.
[0051] The thickness of the oxide battery half-cell prepared by the present invention is 210-700 μm, wherein the thickness of the fuel electrode support layer is 200-600 μm, the thickness of the fuel electrode is 5-50 μm, and the thickness of the electrolyte is 5-50 μm.
[0052] The embodiment of the present invention also provides a method for preparing a solid oxide battery, comprising: a solid oxide half-cell prepared by the above-mentioned preparation method; preparing an oxygen electrode functional layer on the surface of the electrolyte layer of the solid oxide half-cell by screen printing, and then sintering at a temperature of 1000-1150°C for 1.5-3.0h. In the embodiment of the present invention, ethyl cellulose and pinene alcohol are mixed in a mass ratio of 1:10 to obtain a carrier, 30g BSCF is weighed, 20-40wt% of the carrier of the mass of BSCF is added to prepare an oxygen electrode slurry, screen-printed on the surface of the electrolyte layer, and then sintered at 1100°C for 2h to obtain a solid oxide battery. The solid oxide battery prepared in this application has certain restrictions on the sintering temperature of the oxygen electrode, mainly to prevent the excessive temperature from affecting the components of the Ni-Fe and Ni-Cu alloy layers generated after reduction close to the ceramic phase, and reducing the bonding strength between the Ni particles and the ceramic phase.
[0053] For ease of understanding, the present application adopts a membrane belt casting machine to prepare the fuel electrode support layer, the functional layer and the electrolyte casting membrane.
[0054] The prepared solid oxide battery was characterized by electrolysis mode at 750 °C and a constant current density of 1.00 Acm -2 90% H2O / 10% H2 was injected into the fuel electrode, and pure O2 was injected into the oxygen electrode. The degradation rate was calculated by collecting voltage information within 1000h, and the voltage at 1000h was recorded.
[0055] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] This embodiment provides a method for preparing a solid oxide battery, comprising:
[0058] S20 prepares a fuel electrode support layer.
[0059] NiO powder and 3YSZ powder were mixed in a mass ratio of 56:44, and dispersants, plasticizers and binders were added to prepare a fuel electrode support layer casting slurry. An appropriate amount of zirconium oxide ball milling beads were added and ball milled for 36 hours. Subsequently, a membrane belt casting machine was used to prepare the fuel electrode support layer.
[0060] S21 prepares a fuel electrode.
[0061] The NiO powder was immersed in a 1 mol / L ferric nitrate solution and stirred on a magnetic stirrer at 90°C and 400 r / min for 3 h. The solid product obtained after filtration was dried and heat treated at 150°C and calcined at 800°C in a muffle furnace for 5 h to obtain Fe2O3 or CuO-coated NiO alloy powder, which was then mixed with 8YSZ powder in a mass ratio of 66:34. A dispersant, a plasticizer and a binder were added to prepare a fuel electrode casting slurry. An appropriate amount of zirconium oxide ball milling beads were added for ball milling for 36 h, and then the fuel electrode was prepared using a membrane belt casting machine.
[0062] S22 prepares an electrolyte layer.
[0063] The electrolyte layer uses 8YSZ, and a dispersant, a plasticizer and a binder are added to prepare an electrolyte layer casting slurry, and then zirconium oxide ball milling beads are added for ball milling for 36 hours, and then a membrane belt casting machine is used to prepare the electrolyte layer.
[0064] S23 performs multi-step hot isostatic pressing and sintering on the support layer, fuel electrode and electrolyte layer.
[0065] The three-layer cast membrane is stacked according to the support layer cast membrane | functional layer cast membrane | electrolyte cast membrane, and then the isostatic press is used for multi-step hot pressing at 80°C and 30Mpa pressure to prepare the solid oxide battery half-cell blank. The hot-pressed half-cell is placed in a muffle furnace, first slowly heated for debinding treatment, and then heated to 1400°C for sintering for 10 hours.
[0066] S24 Ethyl cellulose and pinene alcohol were mixed in a mass ratio of 1:10 to obtain a carrier, 30 g of BSCF was weighed, 30 wt% of the carrier by mass of BSCF was added to prepare an oxygen electrode slurry, which was screen-printed on the surface of the electrolyte layer, and then sintered at 1100°C for 2 h to obtain a solid oxide battery.
[0067] After the prepared solid oxide battery is reduced in a reducing atmosphere, Figure 3 As shown, the thickness of the Ni-Fe alloy layer is 50 nm.
[0068] The prepared solid oxide battery was used for electrolysis of water, and the degradation rate was 0.022V / kh, and the voltage at 1000h was 1.2V. The organizational morphology of the prepared solid oxide battery was observed by SEM, such as Figure 4 As shown, there are no cracks in the Ni particles and 8YSZ in the fuel electrode of the prepared solid oxide battery.
[0069] Example 2
[0070] This embodiment provides a method for preparing a solid oxide battery, comprising:
[0071] S20 prepares a fuel electrode support layer.
[0072] NiO powder and 3YSZ powder were mixed in a mass ratio of 56:40, and dispersants, plasticizers and binders were added to prepare a fuel electrode support layer casting slurry. An appropriate amount of zirconium oxide ball milling beads were added and ball milled for 36 hours. Subsequently, a membrane belt casting machine was used to prepare the fuel electrode support layer.
[0073] S21 prepares a fuel electrode.
[0074] The NiO powder was immersed in a 0.5 mol / L ferric nitrate solution and stirred on a magnetic stirrer at 70°C and 300 r / min for 3 h. The solid product obtained after filtration was dried and heat treated at 120°C and calcined in a muffle furnace at 700°C for 5 h to obtain a NiFe alloy powder. The powder was then mixed with 8YSZ powder in a mass ratio of 66:30, and a dispersant, a plasticizer and a binder were added to prepare a fuel electrode casting slurry. An appropriate amount of zirconium oxide ball milling beads were added for ball milling for 36 h, and then the fuel electrode was prepared using a membrane belt casting machine.
[0075] S22 prepares an electrolyte layer.
[0076] The electrolyte layer uses 8YSZ, and a dispersant, a plasticizer and a binder are added to prepare an electrolyte layer casting slurry, and then zirconium oxide ball milling beads are added for ball milling for 36 hours, and then a membrane belt casting machine is used to prepare the electrolyte layer.
[0077] S23 performs multi-step hot isostatic pressing and sintering on the support layer, fuel electrode and electrolyte layer.
[0078] The three-layer cast membrane is stacked according to the support layer cast membrane | functional layer cast membrane | electrolyte cast membrane, and then the isostatic press is used for multi-step hot pressing at 50°C and 10Mpa pressure to prepare the solid oxide battery half-cell blank. The hot-pressed half-cell is placed in a muffle furnace, first slowly heated for debinding treatment, and then heated to 1200°C for sintering for 5h.
[0079] S24 Ethyl cellulose and pinene alcohol were mixed in a mass ratio of 1:10 to obtain a carrier, 30 g of BSCF was weighed, 20 wt% of the carrier by mass of BSCF was added to prepare an oxygen electrode slurry, which was screen-printed on the surface of the electrolyte layer and then sintered at 1100°C for 1.5 h to obtain a solid oxide battery.
[0080] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Fe alloy layer was 12 nm. The prepared solid oxide battery was electrolyzed with water, and the degradation rate was 0.023 V / kh, and the voltage at 1000 h was 1.2 V. The organizational morphology of the prepared solid oxide battery was observed by SEM, and there were no cracks in the Ni particles and 8YSZ in the fuel electrode of the prepared solid oxide battery.
[0081] Example 3
[0082] This embodiment provides a method for preparing a solid oxide battery, comprising:
[0083] S20 prepares a fuel electrode support layer.
[0084] NiO powder and 3YSZ powder were mixed in a mass ratio of 56:50, and dispersants, plasticizers and binders were added to prepare a fuel electrode support layer casting slurry. An appropriate amount of zirconium oxide ball milling beads were added and ball milled for 36 hours. Subsequently, a membrane belt casting machine was used to prepare the fuel electrode support layer.
[0085] S21 prepares a fuel electrode.
[0086] The NiO powder was immersed in a 2 mol / L ferric nitrate solution and stirred on a magnetic stirrer at 120°C and 500 r / min for 3 h. The solid product obtained after filtration was dried and heat treated at 120°C and calcined at 900°C in a muffle furnace for 6 h to obtain a NiFe alloy powder. The powder was then mixed with 8YSZ powder in a mass ratio of 66:40, and a dispersant, a plasticizer and a binder were added to prepare a fuel electrode casting slurry. An appropriate amount of zirconium oxide ball milling beads were added for ball milling for 36 h, and then the fuel electrode was prepared using a membrane belt casting machine.
[0087] S22 prepares an electrolyte layer.
[0088] The electrolyte layer uses 8YSZ, and a dispersant, a plasticizer and a binder are added to prepare an electrolyte layer casting slurry, and then zirconium oxide ball milling beads are added for ball milling for 36 hours, and then a membrane belt casting machine is used to prepare the electrolyte layer.
[0089] S23 performs multi-step hot isostatic pressing and sintering on the support layer, fuel electrode and electrolyte layer.
[0090] The three-layer cast membrane is stacked according to the support layer cast membrane | functional layer cast membrane | electrolyte cast membrane, and then the isostatic press is used for multi-step hot pressing at 85°C and 60Mpa pressure to prepare the solid oxide battery half-cell blank. The hot-pressed half-cell is placed in a muffle furnace, first slowly heated for debinding treatment, and then heated to 1500°C for sintering for 20 hours.
[0091] S24 Ethyl cellulose and pinene alcohol were mixed in a mass ratio of 1:10 to obtain a carrier, 30 g of BSCF was weighed, 40 wt% of the carrier by mass of BSCF was added to prepare an oxygen electrode slurry, which was screen-printed on the surface of the electrolyte layer and then sintered at 1150°C for 3 h to obtain a solid oxide battery.
[0092] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Fe alloy layer was 70nm. The prepared solid oxide battery was electrolyzed with water, and the degradation rate was 0.020V / kh, and the voltage at 1000h was 1.25V. There were no cracks between the Ni particles and 8YSZ in the fuel electrode of the prepared solid oxide battery.
[0093] Example 4
[0094] This embodiment provides a method for preparing a solid oxide battery, comprising:
[0095] S20 prepares a fuel electrode support layer.
[0096] NiO powder and 3YSZ powder were mixed in a mass ratio of 56:44, and dispersants, plasticizers and binders were added to prepare a fuel electrode support layer casting slurry. An appropriate amount of zirconium oxide ball milling beads were added and ball milled for 36 hours. Subsequently, a membrane belt casting machine was used to prepare the fuel electrode support layer.
[0097] S21 prepares a fuel electrode.
[0098] The NiO powder was immersed in a 1 mol / L ferric nitrate solution, stirred on a magnetic stirrer at 90°C and 400 r / min for 3 h, the solid product obtained by filtering was dried and heat treated at 150°C, and was placed in a muffle furnace and calcined at 800°C for 5 h to obtain a NiFe alloy powder intermediate. The following process was repeated three times: the NiFe alloy powder intermediate was immersed in a 1 mol / L ferric nitrate solution, stirred on a magnetic stirrer at 90°C and 400 r / min for 3 h, the solid product obtained by filtering was dried and heat treated at 150°C, and was placed in a muffle furnace and calcined at 800°C for 5 h to finally obtain a NiFe alloy powder, which was then mixed with 8YSZ powder in a mass ratio of 66:34, a dispersant, a plasticizer and a binder were added to prepare a fuel electrode casting slurry, an appropriate amount of zirconium oxide ball milling beads were added for ball milling for 36 h, and then a film belt casting machine was used to prepare the fuel electrode.
[0099] S22 prepares an electrolyte layer.
[0100] The electrolyte layer uses 8YSZ, and a dispersant, a plasticizer and a binder are added to prepare an electrolyte layer casting slurry, and then zirconium oxide ball milling beads are added for ball milling for 36 hours, and then a membrane belt casting machine is used to prepare the electrolyte layer.
[0101] S23 performs multi-step hot isostatic pressing and sintering on the support layer, fuel electrode and electrolyte layer.
[0102] The three-layer cast membrane is stacked according to the support layer cast membrane | functional layer cast membrane | electrolyte cast membrane, and then the isostatic press is used for multi-step hot pressing at 80°C and 30Mpa pressure to prepare the solid oxide battery half-cell blank. The hot-pressed half-cell is placed in a muffle furnace, first slowly heated for debinding treatment, and then heated to 1400°C for sintering for 10 hours.
[0103] S24 Ethyl cellulose and pinene alcohol were mixed in a mass ratio of 1:10 to obtain a carrier, 30 g of BSCF was weighed, 30 wt% of the carrier by mass of BSCF was added to prepare an oxygen electrode slurry, which was screen-printed on the surface of the electrolyte layer, and then sintered at 1100°C for 2 h to obtain a solid oxide battery.
[0104] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Fe alloy layer was 195nm. The prepared solid oxide battery was subjected to water electrolysis, and the degradation rate was 0.020V / kh, and the voltage at 1000h was 1.28V. There were no cracks between the Ni particles and 8YSZ in the fuel electrode of the prepared solid oxide battery.
[0105] Example 5
[0106] This embodiment provides a method for preparing a solid oxide battery, comprising:
[0107] S20 prepares a fuel electrode support layer.
[0108] NiO powder and 3YSZ powder were mixed in a mass ratio of 56:50, and dispersants, plasticizers and binders were added to prepare a fuel electrode support layer casting slurry. An appropriate amount of zirconium oxide ball milling beads were added and ball milled for 36 hours. Subsequently, a membrane belt casting machine was used to prepare the fuel electrode support layer.
[0109] S21 prepares a fuel electrode.
[0110] The NiO powder was immersed in a 2 mol / L copper nitrate solution and stirred on a magnetic stirrer at 120°C and 500 r / min for 3 h. The solid product obtained after filtration was dried and heat treated at 120°C and calcined at 900°C in a muffle furnace for 6 h to obtain a NiCu alloy powder. The powder was then mixed with 8YSZ powder in a mass ratio of 66:40, and a dispersant, a plasticizer and a binder were added to prepare a fuel electrode casting slurry. An appropriate amount of zirconium oxide ball milling beads were added for ball milling for 36 h, and then the fuel electrode was prepared using a membrane belt casting machine.
[0111] S22 prepares an electrolyte layer.
[0112] The electrolyte layer uses 8YSZ, and a dispersant, a plasticizer and a binder are added to prepare an electrolyte layer casting slurry, and then zirconium oxide ball milling beads are added for ball milling for 36 hours, and then a membrane belt casting machine is used to prepare the electrolyte layer.
[0113] S23 performs multi-step hot isostatic pressing and sintering on the support layer, fuel electrode and electrolyte layer.
[0114] The three-layer cast membrane is stacked according to the support layer cast membrane | functional layer cast membrane | electrolyte cast membrane, and then the isostatic press is used for multi-step hot pressing at 50°C and 60Mpa pressure to prepare the solid oxide battery half-cell blank. The hot-pressed half-cell is placed in a muffle furnace, first slowly heated for debinding treatment, and then heated to 1500°C for sintering for 10 hours.
[0115] S24 Ethyl cellulose and pinene alcohol were mixed in a mass ratio of 1:10 to obtain a carrier, 30 g of BSCF was weighed, 30 wt% of the carrier by mass of BSCF was added to prepare an oxygen electrode slurry, which was screen-printed on the surface of the electrolyte layer, and then sintered at 1100°C for 3 h to obtain a solid oxide battery.
[0116] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Cu alloy layer was 150nm. The prepared solid oxide battery was used for electrolysis of water at a current density of 1A / cm 2 , no cracks appeared after running at 750℃ for 1000h, and there were no cracks in the Ni particles and 8YSZ in the fuel electrode of the prepared solid oxide battery.
[0117] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Cu alloy layer was 150nm. The prepared solid oxide battery was subjected to water electrolysis, and the degradation rate was 0.020V / kh, and the voltage at 1000h was 1.21V. There were no cracks between the Ni particles and 8YSZ in the fuel electrode of the prepared solid oxide battery.
[0118] Comparative Example 1
[0119] Compared with Example 1, the difference is that in step S21, the NiO powder is immersed in a 0.4 mol / L ferric nitrate solution.
[0120] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Fe alloy layer was 9 nm. The prepared solid oxide battery was used for electrolysis of water, and the degradation rate was 0.201 V / kh, and the voltage at 1000 h was 1.45 V.
[0121] Comparative Example 2
[0122] Compared with Example 4, the difference is that in step S21, the following process is repeated four times: the NiFe alloy powder intermediate is immersed in a 1 mol / L ferric nitrate solution, stirred on a magnetic stirrer at 90°C and 400 r / min for 3 hours, the solid product obtained by filtering is dried and heat-treated at 150°C, and placed in a muffle furnace and calcined at 800°C for 5 hours.
[0123] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Fe alloy layer was 210 nm. The prepared solid oxide battery was used for electrolysis of water, and the degradation rate was 0.020 V / kh, and the voltage at 1000 h was 1.5 V.
[0124] Comparative Example 3
[0125] Compared with Example 1, the difference is that in step S23, the temperature is first slowly increased to perform a debinding process, and then the temperature is increased to 1500° C. and sintered for 22 hours.
[0126] After the prepared solid oxide battery was reduced in a reducing atmosphere, the thickness of the Ni-Fe alloy layer was 210nm. The prepared solid oxide battery was used for electrolysis of water, and the degradation rate was 0.021V / kh, and the voltage at 1000h was 1.48V.
[0127] Comparative Example 4
[0128] Compared with Example 1, the difference is that in step S23, the temperature is first slowly increased to perform a debinding process, and then the temperature is increased to 1150° C. and sintered for 22 hours.
[0129] The prepared solid oxide cell was used to electrolyze water, with a degradation rate of 0.221 V / kh and a voltage of 1.51 V at 1000 h.
[0130] It can be seen from Examples 1, 4 and Comparative Examples 1 and 2 that a smaller or larger thickness of the Ni-Fe alloy layer will result in a higher voltage of the product at 1000h. The reason is that a smaller thickness results in a lower bonding strength between the Ni particles and the ceramic matrix, which generates cracks during the electrolysis process, increases the internal resistance, and causes a voltage increase. A larger thickness results in a lower electrochemical activity of the solid oxide battery, and although the degradation rate is lower, the voltage is higher. It can be seen from Example 1 and Comparative Examples 3 and 4 that the sintering temperature and time are very critical, which controls the diffusion distance between the Ni-Fe elements to reduce the Ni content of the Ni-Fe alloy layer close to the ceramic matrix and improve the wettability of the Ni particles and the ceramic matrix.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A solid oxide fuel cell electrode, characterized in that: In a reducing atmosphere, the fuel electrode of the solid oxide cell comprises Ni particles and an oxygen ion conductor oxide, wherein the surface of the Ni particles has a Ni-Fe or Ni-Cu alloy layer; The thickness of the Ni-Fe or Ni-Cu alloy layer is 10-200nm.
2. The solid oxide fuel cell electrode according to claim 1, characterized in that: The oxygen ion conductor oxide is YSZ or GDC.
3. The method for preparing a solid oxide fuel cell fuel electrode according to claim 1 or 2, characterized in that: include: preparing alloy powder; Mixing the alloy powder with oxygen ion conductor oxide powder to prepare a fuel electrode membrane; Sintering the fuel electrode membrane to obtain; The fuel electrode as claimed in claim 1 or 2 can be obtained under a reducing atmosphere.
4. The preparation method according to claim 3, characterized in that: The preparation method of the alloy powder comprises: Mixing NiO powder with a nitrate solution of Fe or Cu, separating the solid, drying and calcining the solid to obtain alloy powder; or The NiO powder is mixed with a nitrate solution of Fe or Cu, the solid is separated and dried, and then calcined to obtain an alloy powder intermediate; the following process is repeated no more than three times: the alloy powder intermediate is mixed with a nitrate solution of Fe or Cu, the solid is separated and dried and calcined; finally, the alloy powder is obtained.
5. The preparation method according to claim 4, characterized in that: The NiO powder is immersed in a 0.5-2.0 mol / L Fe or Cu nitrate solution, stirred at 70-120° C. and 300-500 r / min for at least 3 hours; and after drying, calcined at 700-900° C. for 5-6 hours.
6. The preparation method according to claim 3, characterized in that: The preparation of a fuel electrode membrane by mixing alloy powder with oxygen ion conductor oxide powder includes: The alloy powder and the oxygen ion conductor oxide powder are added in a mass ratio of 66:(30-40), and a binder, a plasticizer and a dispersant are added to obtain a fuel electrode slurry and a fuel electrode membrane.
7. The preparation method according to claim 3, characterized in that: The fuel electrode membrane sintering process is: heating to 1200-1500° C. at a rate of no more than 20° C. / min and maintaining for 5-20 hours.
8. A method for preparing a solid oxide half-cell, characterized in that: include: preparing a fuel electrode support layer; Prepare a fuel electrode, wherein the fuel electrode is the fuel electrode according to claim 1 or 2 or the fuel electrode prepared by any preparation method according to claim 3-7; preparing an electrolyte layer; The fuel electrode support layer, the fuel electrode and the electrolyte layer are subjected to a multi-step hot isostatic pressing treatment and sintered to obtain the fuel electrode support layer, the fuel electrode and the electrolyte layer.
9. The preparation method according to claim 8, characterized in that: The hot isostatic pressing process is: maintaining the temperature at 50-85° C. and a pressure of 10-60 MPa for at least 30 minutes.
10. A method for preparing a solid oxide battery, characterized in that: include: A solid oxide half-cell prepared by the preparation method according to any one of claims 8 to 9; The oxygen electrode functional layer is prepared on the surface of the electrolyte layer of the solid oxide half-cell by screen printing, and then sintered at a temperature of 1000-1150° C. for 1.5-3.0 hours.
Citation Information
Patent Citations
Preparation method of Ni-Cu coated electrolyte material
CN103367783A
Carbon deposition-resistant solid oxide fuel cell anode and preparation method thereof
CN106450352A
Solid oxide fuel cell metal connector with double-layer coating and preparation method thereof
CN111146486A
Preparation method of SOFC anti-carbon deposition Ni-YSZ anode material
CN111769296A
High-activity anti-carbon-deposition liquid fuel solid oxide fuel cell anode with self-hydration capability and preparation and application of high-activity anti-carbon-deposition liquid fuel solid oxide fuel cell anode
CN115966708A
